Antibiotic Resistance of Enteric Bacteria in HIV-Infected Patients at the Banka Ad-Lucem Hospital, West Region of Cameroon - Ornella J. T. Ngalani; Armelle T. Mbaveng; Wiliane J. T. Marbou; Roland Y. Ngai; Victor Kuete (Canadian Journal of Infectious Diseases and Medical Microbiology)
Human immunodeficiency virus (HIV) infection is a serious problem throughout the world and especially in developing countries. This study was conducted to define the bacterial aetiologies of enteric disorders and their association with CD4+ T-lymphocyte cell count and serum hs-CRP in HIV-seropositive patients coming for consultation at the AD-Lucem Banka Hospital. Stool samples from one-hundred HIV-positive patients with enteric disorders and forty HIV negative patients with enteric disorders were examined for the presence of bacteria by different diagnostic techniques. CD4+ T-lymphocyte count and serum hs-CRP of HIV-positive and HIV-negative patients were examined, respectively, by flux cytometry and the ELISA solid-phase direct sandwich method. Among all the participants, 39 (26.35%) were males and 109 (73.65%) were females. HIV-seropositive mean age (43.79 years) was significantly higher compared to HIV-seronegative (27.13 years) patients (p<0.000). The average values of CD4+ T-cell count (p<0.0001), lymphocytes (p=0.0258), monocytes (p=0.0317), and total WBC count (p=0.0277) were significantly higher in HIV− patients compared to HIV+ patients. Salmonella sp., Escherichia coli, and Klebsiella pneumoniae were more isolated in HIV+ patients 5 (83.33), 18 (75.00), and 37 (71.15) compared to HIV− patients 1 (16.67), 6 (25.00), and 15 (28.85), respectively. Majority of isolates were susceptible to IPM, NOR, and CIP. Klebsiella pneumoniae, the most prevalent isolate, showed resistance to AMC (45.95) in HIV+ patients, whereas in HIV− patients, Enterobacter aerogenes and Shigella sp. showed resistance to AMC (80.00% and 85.71%, respectively) and to CFM (80.00% and 57.14%, respectively). Enterobacter aerogenes (40.00%) and Shigella sp. (14.29) isolates showed multidrug resistance in HIV− patients, whereas Escherichia coli (5.56%) and Klebsiella pneumoniae (2.70%) showed multidrug resistance in HIV+ patients. Understanding the burden of bacteria disease in HIV patients as shown in the present study is important for planning effective control programs for the overall reduction of bacteria diseases in HIV-infected patients.